2022
DOI: 10.1590/1984-0462/2022/40/2020205
|View full text |Cite
|
Sign up to set email alerts
|

Movement Assessment Battery for Children-Second Edition: Theoretical Adequacy of a Motor Assessment Instrument

Abstract: Objective: To investigate the adequacy of the theoretical model of the Movement Assessment Battery for Children-Second Edition (MABC-2) instrument. Methods: 582 children, of both sexes, aged between 3 and 5 years and residents in the city of Maringá (state of Paraná, Southern Brazil) participated in the study. Data were collected from May/2014 to June/2015 and analyzed using descriptive and inferential statistics. Results: The evidence obtained from exploratory factor analysis indicated the presence of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a study carried out in China, the authors concluded that the reproducibility and validity of band 1 of the MABC-2 were poor, emphasizing the need to adjust part of the items to improve the psychometric properties of the test when applied to Chinese children aged 3 to 6 years [74]. For example, studies have shown that, in the Manual Dexterity dimension of band 1, the bike trail task showed low correlation with the threading beads task [57,74,76,77], and the reliability value increased when the bike trail item was removed from the analysis [63,64,68]. Regarding the classification of the child's motor performance, a study carried out in the Netherlands [69], in which the original cut-off points for the diagnosis of motor disorder were maintained (≤7), the study concluded that there would be a higher number of children classified with motor disorder than expected, ranging from 16.2 to 31.3%, depending on the motor task evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study carried out in China, the authors concluded that the reproducibility and validity of band 1 of the MABC-2 were poor, emphasizing the need to adjust part of the items to improve the psychometric properties of the test when applied to Chinese children aged 3 to 6 years [74]. For example, studies have shown that, in the Manual Dexterity dimension of band 1, the bike trail task showed low correlation with the threading beads task [57,74,76,77], and the reliability value increased when the bike trail item was removed from the analysis [63,64,68]. Regarding the classification of the child's motor performance, a study carried out in the Netherlands [69], in which the original cut-off points for the diagnosis of motor disorder were maintained (≤7), the study concluded that there would be a higher number of children classified with motor disorder than expected, ranging from 16.2 to 31.3%, depending on the motor task evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The threading beads test evaluates the ability to thread cubes on a string, with a metal pointed tip, as quickly as possible (6 cubes for children aged 3 and 4 years and 12 cubes for children aged 5 and 6 years). Studies have shown high correlations between the threading beads test and insert coins test [57][58][59]. High correlations between tests indicate that they are measuring the same abilities; on the other hand, if the correlations are low, they would be measuring different abilities [60].…”
Section: Pdms-2mentioning
confidence: 99%